Structural evaluation of flexible pavements using impact deflectometer - Ocana Ortiz, Freddy Arturo; Cruz Rubio, Oscar Fabricio (Universidad Ciencia y Tecnología, 2022)
For this study, an analysis was carried out on eight (8) roads of the fifth (5) town of Usme in the city of Bogotá, which were built with conventional pavement structures (granular bases and granular sub-bases) and others that were intervened with recycled materials - RAP. Lately, it has been chosen to carry out techniques for high-performance tests, known as non-destructive tests, Among these tests, the use of the FWD impact deflectometer stands out, whose function is to analyze the structural condition of the pavements by interpreting the deflections produced under dynamic loads that simulate the effect of traffic and then perform retro calculations that are evaluated at through indicators to obtain modules and structural numbers. Keywords: RAP, Back calculation, Resilient modulus, Deflectometry, Pavement.